Modul program intervensi keluarga untuk pengurangan risiko pengedaran dadah melalui internet dan media sosial di kalangan remaja Malaysia - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Alwi, Azlin; Mohamed Iqbal, Mimi Iznita (2019)
This is a newly developed Family Intervention Module. The objective of the module is to enhance knowledge and skills among parents and adolescents in reducing the risks of online drug trafficking. Although there are many family intervention modules to prevent or mitigate drug abuse among adolescents available, this module is unique and relevant in addressing contemporary issues relating to online drug abuse, particularly involving social media or social networking sites such as WeChat, WhatsApp, etc. Because adolescents are the leading Internet and social media users, they are at a higher risk of being influenced by these drug dealers. This new family intervention module incorporates conventional and new interventions, with one sub-module for parents or carers and another sub-module for adolescents.